Monitoring Technology obtaining cellulolytic enzymes for cellulosic ethanol production - Bofill Rodríguez, Yanet; Mesa Garriga, Leyanis; González Suárez, Erenio; Herrera Coello, Nelsy (Centro Azúcar Journal, 2009)
The production of enzymes by bioprocesses is an alternative to add value to lignocellulosic biomass. Sugar cane bagasse is an abundant by-product of sugar industry and has been tested as support and carbon source for production of cellulolytic enzymes into ethanol process. The techniques used are solid state fermentation and fermentation submerged where the microorganisms degrade the cellulose. The strains whit better cellulolytic activities are Trichoderma reesei mutant and parental, Trichoderma harzianum and Penicillium echinulatum.